Changes between Version 4 and Version 5 of u/johannjc/scratchpad13
- Timestamp:
- 03/11/16 14:08:43 (9 years ago)
Legend:
- Unmodified
- Added
- Removed
- Modified
-
u/johannjc/scratchpad13
v4 v5 1 $\psi - \log \psi - 1 = 4 \left ( \Xi^{-1} - \log {\Xi^{-1}} - 1 \right ) $2 3 4 When $\Xi^{-1} >> 1 $ we have5 6 $ -\log \psi = 4\Xi^{-1}$ or $\psi = e^{-4/\Xi}$7 8 When $\Xi^{-1} << 1$ we have9 10 $\psi = -4 \log \Xi^{-1} = 4 \log \Xi$11 12 When $\Xi \sim 1$ we have13 14 $\psi - (\psi - 1) + (\psi-1)^2/2 - 1 = 4(\Xi^{-1} - (\Xi^{-1}-1)+ (\Xi^{-1}-1)^2/2 - 1)$15 16 $(\psi-1)^2/2 = 2 (\Xi^{-1}-1)^2$17 18 $\psi= 1 + 2 (\Xi^{-1}-1)$19 20 1 21 2 == Vis-visa equation ==